Tpz1TPP1 SUMOylation reveals evolutionary conservation of SUMO‐dependent Stn1 telomere association. (12th June 2014) - Garg, Mansi; Gurung, Resham L; Mansoubi, Sahar; Ahmed, Jubed O; Davé, Anoushka; Watts, Felicity Z; Bianchi, Alessandro
Abstract Elongation of the telomeric overhang by telomerase is counteracted by synthesis of the complementary strand by the CST complex, CTC1(Cdc13)/Stn1/Ten1. Interaction of budding yeast Stn1 with overhang‐binding Cdc13 is increased by Cdc13 SUMOylation. Human and fission yeast CST instead interact with overhang‐binding TPP1/POT1. We show that the fission yeast TPP1 ortholog, Tpz1, is SUMOylated. Tpz1 SUMOylation restricts telomere elongation and promotes Stn1/Ten1 telomere association, and a SUMO‐Tpz1 fusion protein has increased affinity for Stn1. Our data suggest that SUMO inhibits telomerase through stimulation of Stn1/Ten1 action by Tpz1, highlighting the evolutionary conservation of the regulation of CST function by SUMOylation.